ACOG Clinical Practice Guideline No. 12: Obstetric Cerclage (Obstetrics & Gynecology, 2026)
PURPOSE: The purpose of this document is to provide evidence-based indications, surgical techniques, alternatives, and management strategies for cervical cerclage in pregnancy. TARGET POPULATION: Patients with an indication for cervical cerclage, including cervical insufficiency, prior obstetric history, and cervical shortening. METHODS: This guideline was developed using an a priori protocol in conjunction with a writing team consisting of three maternal–fetal medicine subspecialists appointed by the American College of Obstetricians & Gynecologists' (ACOG's) Committee on Clinical Practice Guidelines–Obstetrics. ACOG medical librarians completed a comprehensive literature search for primary literature within Cochrane Library, Cochrane Collaboration Registry of Controlled Trials, EMBASE, PubMed, and MEDLINE. Studies that moved forward to the full-text screening stage were assessed by the writing team based on standardized inclusion and exclusion criteria. Included studies underwent quality assessment, and a modified GRADE (Grading of Recommendations Assessment, Development and Evaluation) evidence-to-decision framework was applied to interpret and translate the evidence into recommendation statements. RECOMMENDATIONS: This Clinical Practice Guideline provides recommendations for cervical cerclage indications, surgical approach, and management, as well as alternative therapies. Recommendations are classified by strength and evidence quality.